The Struggle for Recognition: A Study of the Existence of the Indonesian Ahmadiyya Community in the Concept of Axel Honneth's Recognition - Ahmad, Mubarak; Bunyamin, Bunyamin; Nawawi, Muhammad Azhar; Pratama, Cahya Adhitya; Junior, Rizkindo (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
Abstract: The Indonesian Ahmadiyya Congregation (JAI) is one of the Islamic organizations in Indonesia that has developed through a historical process. JAI has struggled to gain recognition from the community, such as social programs and the law's legality. However, JAI remains the target of intolerant groups to carry out persecution because the teachings adhered to by JAI are considered heretical due to different Islamic concepts in general. This study aims to analyze the existence of JAI, such as legal entities, organizational systems, and activities carried out. This study uses a qualitative descriptive method with an interview approach and a literature study. The study results indicate a legal clash between the legality of JAI's law and the law that prohibits JAI's activities. Then the general public does not seek information beforehand about the Indonesian Ahmadiyya Congregation, so the public is consumed by the issues addressed to the Indonesian Ahmadiyya Congregation.